Evaluation of immersion 20 MHz B-scan ultrasonography in observing lens in the alkali burn eyes - Yang, Qing-Hua (International Journal of Ophthalmology Press, 2014)
AIM: To evaluate the accuracy of 20 MHz immersion B-scan ultrasonography in observing lens and to investigate the value of this noninvasive preoperative diagnosis method in alkali burn eyes. METHODS: It was a comparative study. Fifty-six cases (56 eyes) of alkali burn eyes were examined by ultrasound biomicroscopy (UBM) and immersion 20 MHz B-scan ultrasonography from June 2011 to April 2013, the images were analyzed, and the ultrasonographic diagnosis compared with the operation results. RESULTS: In 56 alkali burn eyes examined by UBM, the lens were not detected in 16 eyes; the IOL could be detected in 2 eyes; the anterior lens capsule surface or/and the front lens could be detected in 18 eyes, and lens opacification in 3 eyes of them; suspected abnormal lens were detected in the other 20 eyes. In all the same eyes examined by immersion 20 MHz B-scan ultrasonography, the lens were not detected in 16 eyes; the IOL could be detected in 2 eyes; 24 abnormal lens (opacity, lens expansion, shrinkage) and 14 normal lens were found. Compared with the intraoperative findings, the diagnostic accordance rate of the immersion 20 MHz B-scan appearance of lens was 100% (56/56), which was significantly higher than examined by UBM 57.14% (32/56) (χ(2)=30.55, P=0.0000). CONCLUSION: Immersion 20 MHz B-scan ultrasonography can observe the lens accurately in alkali burn eyes. It has important clinical value to combine with UBM in eyes of alkali burn.